An Exploration of Charge Compensating Ion Channels across the Phagocytic Vacuole of Neutrophils - Foote, Juliet R.; Behe, Philippe; Frampton, Mathew; Levine, Adam P.; Segal, Anthony W. (Frontiers in Pharmacology, 2017)
Neutrophils phagocytosing bacteria and fungi exhibit a burst of non-mitochondrial respiration that is required to kill and digest the engulfed microbes. This respiration is accomplished by the movement of electrons across the wall of the phagocytic vacuole by the neutrophil NADPH oxidase, NOX2. In this study, we have attempted to identify the non-proton ion channels or transporters involved in charge compensation by examining the effect of inhibitors on vacuolar pH and cross-sectional area, and on oxygen consumption. The chloride channel inhibitors 4-[(2-Butyl-6,7-dichloro-2-cyclopentyl-2,3-dihydro-1-oxo-1H-inden-5-yl)oxy]butanoic acid (DCPIB) and flufenamic acid (FFA) were the most effective inhibitors of alkalinisation in human neutrophil vacuoles, suggesting an efflux of chloride from the vacuole. The proton channel inhibitor, zinc (Zn2+), combined with DCPIB caused more vacuolar swelling than either compound alone, suggesting the conductance of osmotically active cations into the vacuole. Support for cation influx was provided by the broad-spectrum cation transport inhibitors anandamide and quinidine which inhibited vacuolar alkalinisation and swelling when applied with zinc. Oxygen consumption was generally unaffected by these anion or cation inhibitors alone, but when combined with Zn2+ it was dramatically reduced, suggesting that multiple channels in combination can compensate the charge. In an attempt to identify specific channels, we tested neutrophils from knock-out mouse models including CLIC1, ClC3, ClC4, ClC7, KCC3, KCNQ1, KCNE3, KCNJ15, TRPC1/3/5/6, TRPA1/TRPV1, TRPM2, and TRPV2, and double knockouts of CLIC1, ClC3, KCC3, TRPM2, and KCNQ1 with HVCN1, and humans with channelopathies involving BEST1, ClC7, CFTR, and MCOLN1. No gross abnormalities in vacuolar pH or area were found in any of these cells suggesting that we had not tested the correct channel, or that there is redundancy in the system. The respiratory burst was suppressed in the KCC3-/- and enhanced in the CLIC1-/- cells, but was normal in all others, including ClC3-/-. These results suggest charge compensation by a chloride conductance out of the vacuole and by cation/s into it. The identity of these channels remains to be established.